Dosage form design considerations. Volume 1 - Tekade, Rakesh K. (London, United Kingdom : Elsevier, 2018)
Dosage Form Design Parameters, Volume I, examines the history and current state of the field within the pharmaceutical sciences, presenting key developments. Content includes drug development issues, the scale up of formulations, regulatory issues, intellectual property, solid state properties and polymorphism. Written by experts in the field, this volume in the Advances in Pharmaceutical Product Development and Research series deepens our understanding of dosage form design parameters. Chapters delve into a particular aspect of this fundamental field, covering principles, methodologies and the technologies employed by pharmaceutical scientists. In addition, the book contains a comprehensive examination suitable for researchers and advanced students working in pharmaceuticals, cosmetics, biotechnology and related industries.
2.2.1 Crystalline Solid-State Substances2.2.1.1 Polymorphism; 2.2.1.2 Hydrates; 2.2.1.3 Solvates; 2.2.1.4 Cocrystals; 2.2.2 Amorphous Solids; 2.2.3 Particle Size; 2.2.4 Wettability; 2.2.5 Hygroscopicity; 2.3 Chemical Characteristics to be Considered in Pharmaceutical Product Development; 2.3.1 Degradation Reactions of Drugs; 2.3.1.1 Hydrolysis; 2.3.1.2 Dehydration; 2.3.1.3 Oxidation; 2.3.1.4 Photochemical Degradation; 2.3.1.5 Isomerization; 2.3.1.6 Polymerization; 2.3.1.7 Other Reactions; 2.4 Solubility Aspects in Pharmaceutical Products Development; 2.4.1 Aqueous Solubility
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
Includes bibliographical references and index.
Mode of access: Internet
Keywords: Drug delivery systems; Drug development; Drugs -- Design; Drugs -- Dosage forms; Drug delivery systems; Drug development; Drugs -- Design; Drugs -- Dosage forms; MEDICAL / Pharmacology; Electronic books